The Impact of a Teaching Strategy Based on TRIZ Theory on Developing Higher-Order Thinking Skills Among Gifted Students in Mathematics - Hussein Koma, Saja; Ali Hussein, Alaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The research aims to identify the impact of a teaching strategy based on the TRIZ theory on developing higher-order thinking skills among gifted students in mathematics. The sample was selected using a simple random method, consisting of 42 gifted second-grade intermediate students. The two researchers prepared a higher-order thinking skills test, comprising 9 objective items and 3 essay items. The psychometric properties and face validity were verified, and Cronbach’s alpha equation was used to calculate the test’s reliability. The results showed the experimental group’s superiority in the post-test of higher-order thinking skills. Based on these findings, the two researchers presented some recommendations and suggestions.